Trust and the Duty of Organ Donation - Almassi, Ben (Bioethics, 2014)
Several recent publications in biomedical ethics argue that organ donation is generally morally obligatory and failure to do so is morally indefensible. Arguments for this moral conclusion tend to be of two kinds: arguments from fairness and arguments from easy rescue. While I agree that many of us have a duty to donate, in this article I criticize these arguments for a general duty of organ donation and their application to organ procurement policy. My concern is that these arguments neglect the role that trust plays in contemporary organ transplant policies and in differential rational attitudes toward donation. Recognizing donation as an achievement of trust, and acknowledging the warrant of many people's rational distrust or withheld trust in medicine, I argue, should have significant implications for the ethics of organ procurement.